An intelligent production planning support system between bakery enterprises - Limanska, Nataliia; Hrybkov, Serhii; Kostikov, Mykola (My University, 2022)
The paper proposes an intelligent system for production planning support between bakery enterprises. Considering the specifics of bakery enterprises, a mathematical model of profit is proposed. This model takes into account logistical features when distributing orders among several enterprises in this industry. The paper considers the complex task of taking into account the necessary raw materials supply to corresponding factories, as well as the supply of finished products to customers. The proposed mathematical model allows the creation of an order fulfillment plan that takes into account all operations of the technological process in the manufacturing of products. It also allows adjustment and evaluation of the order fulfillment efficiency depending on the objective and subjective advantages provided by the decision maker and allows both consideration and exclusion of certain partial criteria depending on a specific situation. The model makes it possible to estimate and build an operational-calendar order fulfillment plan. The paper analyzes several methods and approaches that are included in the intelligent support system for planning the manufacturing of products between bakery enterprises that belong to the same company or have a cooperation agreement concluded between them, which will make it possible to derive the entire management process to a new level. The proposed information system structure makes it possible to combine the use of modified algorithms and methods based on combining algorithms, which were also analyzed in the work, as well as some classical approaches. The system provides a possibility to select a set of algorithms and methods, which increases the range of applications. The proposed system quickly forms an operational calendar plan for order fulfillment with cost minimization aimed at maximizing profit; enables reduction of logistics costs, which ensures obtaining higher quality products with minimal waiting time; allows quick adjustment of the existing calendar plan of orders, which makes it possible to respond to orders in real-time and ensure optimal use of technological equipment; significantly increases the efficiency of using raw materials, and also ensures the minimization of costs for their storage; ensures a quick response in case of negative and extraordinary situations by making appropriate changes to the current order fulfillment plan.

У роботі запропоновано інтелектуальну система підтримки планування виготовлення продукції між хлібо- пекарними підприємствами. Враховуючі специфіку хлібопекарських підприємств, запропоновано математична модель отримання прибутку. Модель враховує логістичні особливості при розподіленні замовлень між декілько- ма підприємствами цієї галузі. В роботі розглянуто комплексну задачу врахування постачання потрібної сирови- ни на відповідні заводи, а також постачання готової продукції до замовників. Запропонована математична модель дозволяє сформувати план виконання замовлень із урахуванням усіх опе- рацій технологічного процесу при виготовленні продукції. Вона також дозволяє коригувати та оцінювати ефек- тивність виконання замовлень залежно від об’єктивних та суб’єктивних переваг, наданих особою, що приймає рішення, а також забезпечує як урахування, так і виключення певних часткових критеріїв залежно від певної ситуації. Модель дає змогу оцінити та побудувати оперативно-календарний план виконання замовлень. Запропонована структура інформаційної системи дає можливість поєднати використання модифікова- них алгоритмів та методів, заснованих на комбінуванні алгоритмів, які також були проаналізовані в роботі, а також цілої низки класичних підходів. У системі передбачено можливість підібрати сукупність алгоритмів і методів, що збільшує сферу застосування. Запропонована інтелектуальна система швидко формує оперативно-календарний план виконання замовлень із мінімізацією витрат, спрямований на максимізацію прибутку; дає змогу зменшити логістичні витрати, дозво- ляючи отримувати більш якісну продукцію з мінімальним часом очікування; дає змогу оперативно коригувати існуючий календарний план замовлень, реагувати на замовлення в реальному часі та забезпечувати оптимальне використання технологічного обладнання; значно збільшує ефективність використання сировини та матеріа- лів, а також забезпечує мінімізацію витрат на їх зберігання; забезпечує швидке реагування при виникненні нега- тивних та позаштатних ситуацій шляхом внесення відповідних змін до поточного плану виконання замовлень. Ключові слова: штучний інтелект, система підтримки прийняття рішень, інтелектуальна система, мате- матична модель, планування виробництва, хлібопекарське підприємство.
Keywords: intelligent system; artificial intelligence; decision support system; mathematical model; production planning; bakery enterprise; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки; bakery enterprise; планування виробництва; математична модель; система підтримки прийняття рішень; штучний інтелект; інтелектуальна система